The learning-relative hemodynamic modulation of cortical plasticity induced by a force-control motor training - Wang, Yongrong; Feng, Shuai; Yang, Rui; Hou, Wensheng; Wu, Xiaoying; Chen, Lin (Frontiers in Neuroscience, 2022)
Background: Novel motor skills are generally be acquired through repetitive practices which are believed strongly related to the neural plasticity mechanisms. This study aimed to investigate the learning-relative hemodynamic modulation of cortical plasticity induced by long-term motor training. Methods: An 8-day participation-control program was conducted. Eighteen right-handed healthy participants were recruited and randomly assigned into the Training (12) and Control groups (6). The training group were arranged to undergo the 8-day block-designed motor training which required to repeat a visuomotor force-control task. The functional Near Infrared Spectroscopy (fNIRS) were used to continuously monitor the cortical hemodynamic response during training. Two transcranial magnetic stimulation (TMS) measurements were performed before- and after-training to evaluate the cortical excitability changes. The transfer effects of learning were also investigated. Results: The behavior performance was quantified via scores execution accuracy to illustrate the fast/slow learning stages as experience cumulated. The cortical hemodynamic activations mapped by fNIRS exhibited a temporal evolution trends agreed the expansion-renormalization model, which assumed the brain modulation against skill acquisition includes complex mechanism of neural expansion, selection and renormalization. Functional connectivity analysis showed the FC strength maintained while the measured homodynamic activation return to baseline after certain level of skill acquisition. Further, the TMS results demonstrated a significant increase of motion evoked potential (MEP) on the targeted muscle for the trained participants, who significantly outperformed the untrained subjects in learning transfer investigation. Conclusions: The study illustrated the expansion-renormalization trends during continuous motor training, and relative analysis showed the functional connection enhancement may maintained after amplitude renormalization of cortical hemodynamic activations. The TMS findings further gave an implication of neural facilitations on the descending motor pathway when brain activation returned to renormalization status after certain level of learning stages achieved, and the learning can transfer to enhance the performance while encountering similar tasks.